Sports journalism : a practical introduction - Andrews, Phil (Los Angeles, CA. : SAGE, 2014)
The sports journalist of today needs to be well equipped for the digital age. From the challenges of minute-by-minute reporting to the demands of writing for online outlets, blogging and podcasting, sports journalism is now fully immersed in new and social media. this book will give you the skills you need to navigate these new platforms, whilst also teaching you the basics of interviewing, reporting, feature writing for print and commentary for radio and television.
First published: 2005.
Includes bibliographical references and index.
Keywords: Sports journalism